2 Timeline history for secondary level(1000 years of change) - Roberts, Martin (Oxford University Press; UK, 2001)
2 Timeline History for Secondary Level (1000 Years of Change) offers a concise visual journey through key global events and developments over the past millennium, designed to engage and inform students.